TandemTools: mapping long reads and assessing/improving assembly quality in extra-long tandem repeats - Mikheenko, Alla (Bioinformatics, 2020)
MOTIVATION: Extra-long tandem repeats (ETRs) are widespread in eukaryotic genomes and play an important role in fundamental cellular processes, such as chromosome segregation. Although emerging long-read technologies have enabled ETR assemblies, the accuracy of such assemblies is difficult to evaluate since there are no tools for their quality assessment. Moreover, since the mapping of error-prone reads to ETRs remains an open problem, it is not clear how to polish draft ETR assemblies. RESULTS: To address these problems, we developed the TandemTools software that includes the TandemMapper tool for mapping reads to ETRs and the TandemQUAST tool for polishing ETR assemblies and their quality assessment. We demonstrate that TandemTools not only reveals errors in ETR assemblies but also improves the recently generated assemblies of human centromeres. AVAILABILITY AND IMPLEMENTATION: https://github.com/ablab/TandemTools. SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.